Impact of a surgical safety checklist on surgical site infections, antimicrobial resistance, antimicrobial consumption, costs and mortality. (October 2021) - de Almeida, S.M.; de Menezes, F.G.; Martino, M.D.V.; Tachira, C.R.; Toniolo, A.do R.; Fukumoto, H.L.; Edmond, M.B.; Marra, A.R.
Summary: Background: In 2010, following the recommendations of the World Health Organization (WHO), our hospital implemented a surgical safety programme centred around a surgical safety checklist. Aim: The aim of this study was to compare indicators of surgical site infection, antimicrobial consumption, antimicrobial resistance, costs and in-hospital mortality before (January 2006 to July 2010) and after (August 2010 to December 2014) implementation of the programme. Methods: A case–control study was carried out matching patients with surgical site infection (SSI) to surgical patients without infection to examine the impact of the intervention. Findings: Use of the surgical checklist was associated with a significant reduction in SSI. When comparing the two time periods, we also identified a reduction in infections due to micro-organisms in the ESKAPE group (from 90.7% to 73.9%, P <0.001), a reduction of SSI in patients with contaminated, infected and potentially contaminated wounds, and for those in whom perioperative antimicrobial prophylaxis was discontinued in less than 48 hours. Overall, there was a reduction in antimicrobial resistance, though there was increased resistance to carbapenems for, to glycopeptides for Enterococcus faecium, and to clindamycin for Staphylococcus aureus. We also detected increased antimicrobial consumption of second- and third-generation cephalosporins and clindamycin. We observed a reduction in hospital deaths from 6.4% to 3.2% ( P =0.001), but we did not observe any reduction in costs. Conclusions: Implementation of a surgical checklist was an independent predictor of SSI reduction, and was also associated with a decrease in antimicrobial resistance and reduced in-hospital mortality.